Síndrome de Brugada: Las mujeres también tienen riesgo - Castro Hevia, Jesus A.; Dorantes Sánchez, Margarita; Castañeda Chirino, Osmín (CorSalud, 2022)
Síndrome de Brugada: Las mujeres también tienen riesgo